Trump Administration Tightens Procedures with Respect to Asylum Seekers at the Southern Border. Issue 2 (9th April 2019) - Unknown
Abstract : The Trump administration undertook a variety of actions related to the southern U.S. border in late 2018 and early 2019. Pointing to the progress of thousands of migrants traveling together from Central America to the U.S. border, President Trump deployed troops to the border and issued a proclamation providing that access to asylum would only be available at the southern border to those who entered through an authorized port of entry. Legal challenges to this proclamation and its implementation by the Department of Homeland Security (DHS) immediately followed, and a federal district court issued a temporary restraining order on November 19 and a preliminary injunction on December 19 against its enforcement. In addition, after ongoing negotiations with Mexico, the Trump administration announced that it would implement an arrangement under which asylum seekers would await their court date in Mexico rather than the United States. These ongoing developments are part of broader attempts by the Trump administration to erect barriers to migration across the southern border.